“It’s a last straw situation”; Overdose response and preferences for seeking support from emergency services during overdose in rural Ohio - David C. Colston; Vivian F. Go; Clare Barrington; Adams L. Sibley; Hannah M. Piscalko; Laura Limarzi-Klyn; William C. Miller (PLoS ONE, 2026)
Objectives We assessed how people who use drugs in rural Ohio communities affected by the opioid epidemic respond to overdose, their preferences for seeking support from first responders, and factors contributing to their willingness or hesitancy to call 9-1-1 during an overdose. Methodology Semi-structured interviews were conducted in select rural Ohio counties from 2021–2022 as part of the Ohio Opioid Project, one of eight sites in the Rural Opioid Initiative focused on overdose in the rural United States. Forty-four interviews with people who use drugs were coded using thematic analysis. Results Most participants had suffered an overdose (23/43) or witnessed (33/43) an overdose. Most participants preferred not to seek first responder support during an overdose if the victim was able to be revived. As a result, first responder support was not sought in most overdoses experienced or witnessed by participants. When first responders were called, outcomes varied: some participants felt the overdose victim’s lives were saved, others felt stigmatized by first responders, and one was arrested by law enforcement at the scene. Among participants who preferred not to seek support from first responders, fear of arrest, hospitalization, and stigmatization were the main reasons. Significance/Contribution This study details intervenable factors that could prevent overdoses from escalating to fatalities in rural Ohio, including: increasing awareness and knowledge for Good Samaritan Laws to encourage calls to 9-1-1 during overdose, ensuring unlawful arrests are not made at the scene of an overdose, and de-stigmatizing substance use among first responders and health care professionals. Findings may not be generalizable to the entire United States, but may have applicability in other rural, Appalachian areas.